Enfisema ampolloso gigante: a propósito de 7 observaciones personales - Mazzei, Egidio (1943)
Taking for basis 7 personal observations, we study “ampolloso” giant emphysema. We insist in the necessity to take it in consideration before cases wronly named congenital, and we remember that such blisters establish the 3rd. degree in the evolution of the emphysema according to the autors and Remolar classification.